Assessing the influence of structural disorder on the plant epidermal cells' optical properties: a numerical analysis. (4th May 2017) - Fritz, Benjamin; Hünig, Ruben; Schmager, Raphael; Hetterich, Michael; Lemmer, Uli; Gomard, Guillaume
Abstract: Many plant surfaces, such as rose petals, display lens-like epidermal cells that are known to assist the collection and focusing of the sunlight. Those cells form an array with a high degree of structural irregularities including disorder in the height and orientation of the cells, and in their arrangement. In this study, we numerically analyze the influence of structural disorder on the optical properties of a 3D modeled epidermal cell array using ray tracing simulations. We conclude that the anti-reflection properties of such structures are almost unperturbed by disorder effects, although the latter can notably broaden the propagation angle distribution of the collected light. Those results also have a direct implication on the design of plant-inspired light management structures. This aspect is illustrated by introducing the example of a thin-film solar cell covered by a light harvesting epidermal cells replica and simulated for each of the three disorder types considered.